Lipid Biomarkers Quantify Holocene Summer Temperature and Ice Cap Sensitivity in Icelandic Lakes - David J. Harning; Lorelei Curtin; Áslaug Geirsdóttir; William J. D'Andrea; Gifford H. Miller; Julio Sepúlveda (Geophysical Research Letters)
Abstract Although recent research has made significant advances in characterizing Iceland's Holocene environmental history, the region still lacks reliable and continuous records of corresponding paleotemperature. Here we merge bacterial and algal lipid biomarkers (branched glycerol dialkyl glycerol tetraethers and long‐chain alkenones, respectively) to quantify Holocene temperature change from a small lake in northwest Iceland. Our local proxy record shows that early Holocene and late Holocene temperatures ranged from 3.2 to −1.1 oC relative today, which are in close agreement with independent estimates from regional ice cap models. At 2.4 ka, we observe abrupt cooling across bacteria‐, algae‐, and glacier‐derived proxy records, which may have been initiated by extratropical volcanism and/or ocean/atmospheric climate variability of the North Atlantic region. Using early Holocene warmth and ice cap demise as an analog for modern climate change, Intergovernmental Panel on Climate Change temperature projections suggest that the local ice cap, Drangajökull, could vanish by ~2050 CE.